Work and Festa Ferianda in Medieval England - Harvey, Barbara (The journal of ecclesiastical history, 1972)
Much work that is absolutely essential for the continuance and progress of an ordered society has a severely limited attraction for those who perform it. How, nevertheless, men and women were persuaded to work regularly or at all in the Middle Ages has provided one of the central themes in the study of the period, for this is what we study in the institutions of slavery, serfdom and villeinage—all three were ways and means of persuading reluctant workers to work. But these were also means of escape from toil, and it is with one of these, the custom of abstaining from many habitual forms of work on church festivals, that this essay is concerned.